Zakat and Its Impact on Socio-Economic Welfare Before COVID-19 Pandemic in Indonesia - Sulaeman Sulaeman; Rifaldi Majid; Tika Widiastuti (International Journal of Zakat, 2021)
The purpose of this paper is to examine empirically the impact of zakah on socio-economic welfare to enhance the Indonesian economic growth and purchasing power as well as to reduce the level of poverty along with the period 2002-2019 in Indonesia. Through multiple regression methods, the study found zakah has a positive and significant effect to boost economic growth and purchasing power. Zakah also is found to contribute to reducing the level of poverty before pandemic Covid-19 in Indonesia. The results of this study will support that the zakat is not merely benefits to social sectors but also have a positive impact on the economic development of the society. This study will also give an alternative of public policy for the Indonesian government to continuously promote zakah for supporting to achieve national economic recovery during and post-Covid-19 in Indonesia.